Na+ Fuel Cells: Half‐Cell and Full‐Cell Applications of Highly Stable and Binder‐Free Sodium Ion Batteries Based on Cu3P Nanowire Anodes (Adv. Funct. Mater. 28/2016). (25th July 2016) - Fan, Mouping; Chen, Yu; Xie, Yihao; Yang, Tingzhou; Shen, Xiaowei; Xu, Na; Yu, Haiying; Yan, Chenglin
Abstract : The fabrication of additive‐free Cu3 P nanowire anodes for Na + fuel cells is presented by Y. Chen, C. Yan, and co‐workers on page 5019. With a high specific reversible capacity, a good rate performance, and a stable cycling performance the new anode martial is promising for future studies of sodium ion batteries.